Designing and Evaluating a University Web-Based Metaverse: An A-Frame Implementation - Coronado, Angelo; Franco, Guilherme C.; Nascimento, Hugo; Berretta, Luciana; Galvão, Arlindo; Carvalho, Sergio T. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
The Metaverse consists of interconnected 3D shared environments that support a wide range of human activities through diverse technologies and services. In recent years, many enterprises have invested substantial time and resources in developing proprietary Metaverse platforms. However, most of these efforts have resulted in isolated, non-interoperable systems. As a work in progress, this study investigates the potential of a Web-based University Metaverse to be replicated by other institutions and to support future interconnection. The paper presents the implementation of a Web-based Metaverse developed with A-Frame, and also reports preliminary results from a usability evaluation. It also outlines future directions for improving interactivity, and immersion.